Effects of classroom acoustics on speech intelligibility and response time: A comparison between native and non-native listeners. Issue 1 (March 2018) - Lam, Alice; Hodgson, Murray; Prodi, Nicola; Visentin, Chiara
This study evaluates the speech reception performance of native (L1) and non-native (L2) normal-hearing young adults in acoustical conditions containing varying amounts of reverberation and background noise. Two metrics were used and compared: the intelligibility score and the response time, taken as a behavioral measure of listening effort. Listening tests were conducted in auralized acoustical environments with L1 and L2 English-speaking university students. It was found that even though the two groups achieved the same, close to the maximum accuracy, L2 participants manifested longer response times in every acoustical condition, suggesting an increased involvement of cognitive resources in the speech reception process.